2005
DOI: 10.1128/aem.71.10.6443-6445.2005
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ethanol from Starch by Respiration-Deficient Recombinant Saccharomyces cerevisiae

Abstract: A 100%-respiration-deficient nuclear petite amylolytic Saccharomyces cerevisiae NPB-G strain was generated, and its employment for direct fermentation of starch into ethanol was investigated. In a comparison of ethanol fermentation performances with the parental respiration-sufficient WTPB-G strain, the NPB-G strain showed an increase of ca. 48% in both ethanol yield and ethanol productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A spontaneous petite mutant was also observed to ferment wort more slowly and accumulate less biomass, at low cell densities, than that of its respiratory‐competent wild‐type99, 200, 265. Reduced attenuation rates73 but higher ethanol yields132, 265 appear to occur. Spontaneous mutants also appear to modify beer flavour191 by overproducing higher alcohols, such as isobutanol and isoamyl alcohol, and underproducing esters99, 191, 199.…”
Section: Brewing Yeast Genome Instabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…A spontaneous petite mutant was also observed to ferment wort more slowly and accumulate less biomass, at low cell densities, than that of its respiratory‐competent wild‐type99, 200, 265. Reduced attenuation rates73 but higher ethanol yields132, 265 appear to occur. Spontaneous mutants also appear to modify beer flavour191 by overproducing higher alcohols, such as isobutanol and isoamyl alcohol, and underproducing esters99, 191, 199.…”
Section: Brewing Yeast Genome Instabilitymentioning
confidence: 98%
“…Petite mutation affects sugar utilization in brewing strains73, 139. A spontaneous petite mutant was also observed to ferment wort more slowly and accumulate less biomass, at low cell densities, than that of its respiratory‐competent wild‐type99, 200, 265. Reduced attenuation rates73 but higher ethanol yields132, 265 appear to occur.…”
Section: Brewing Yeast Genome Instabilitymentioning
confidence: 99%
“…Regardless of the species, parental microorganisms remain insufficient in conventional ethanol production due to the lack of availability of sugar rich input and low ethanol yields. Over 150 amylolytic yeast strains have been reported to be impractical in industrial use because of limited characteristics [13]. Although Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Hutter and Oliver (18) suggested that 100% respiration-deficient nuclear petites may be used in the commercial production of ethanol under circumstances in which the oxygen supply cannot be tightly controlled. Indeed, the use of respiration-deficient S. cerevisiae strains as hosts for the construction of recombinant strains increased the ethanol yield from starch (38).…”
mentioning
confidence: 99%